Natural fuels (Honey and Cow urine) assisted combustion synthesis of zinc oxide nanoparticles for antimicrobial activities. Issue 10 (15th May 2021) - Ranjithkumar, B.; Ramalingam, H.B.; Kumar, E. Ranjith; Srinivas, Ch.; Magesh, G.; Rahale, C. Sharmila; El-Metwaly, Nashwa M.; Shekar, B. Chandar
Abstract: A novel green synthesis of the combustion pathway was adopted for the preparation of ZnO nanoparticles using Honey and Cow urine. The effects of honey and cow urine on crystalline size, structure, morphology, band gap and thermal properties of ZnO nanoparticles have been analyzed. The polycrystalline hexagonal wurtzite structure of ZnO nanoparticles is confirmed by XRD spectra. The mean crystalline sizes of the ZnO nanoparticles were 23 nm and 29 nm respectively, for the honey and cow urine phase. The external morphology and grain size of the products have been visualized via FE-SEM and TEM. The average sizes of the grains of the ZnO nanoparticles were perfectly associated with the crystalline size measured from the XRD. Spherical and hexagonal shaped nanostructures were reported using FE-SEM and TEM micrographs. The optical absorption spectra of ZnO nanoparticles have been analyzed using UV–Vis spectrometry. In the FT-IR spectra, around 400 cm −1 to 600 cm −1 range have been allotted to the Zn–O vibration. The thermal properties of ZnO nanoparticles have been analyzed using TGA. Changes in weight loss for different ZnO nanoparticles using honey and cow urine have been documented. Gram Positive (B.Subtilis) and Gram-Negative (E.Coli)Bacteria were tested using plate counting technique to study the antimicrobial activity of ZnO nanoparticles prepared by cow's urine and honey. Compared with cow urine-prepared ZnO nanoparticles, honey-assisted ZnO nanoparticles demonstrate strong antibacterial activity.